PENGARUH DISIPLIN KERJA PEGAWAI NEGERI SIPIL TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT BUPATI KABUPATEN KUTAI TIMUR - Nece, Peronika (PREDIKSI, 2016)
The purpose of this research is to know whether the influence of motivation on the performance of the officers in Sekretariat Bupati Kabupaten East Kutai. The analysis used a simple Linier regression test. Using the sampling method is determined by the number of samples as much as 45 employees in Sekretariat Bupati Kabupaten East Kutai, by the data obtained through the questioner.The results of the simple regression analysis between the variables motivation and performance of employees obtained equation Y = 1.83 0,5127 X. Then the value of the correlation r of 0,616. After the results of the analysis of the compared with r table (table critical price) where N = 45 with equal significance 0.05, r count the empirical greater than r table (0,616>0,3059). Thus the hypothesis of work (hi) accepted the truth and reject the hypothesis of zero (ho) This means there is no influence between work motivation with the performance of the officers in Sekretariat Bupati Kabupaten East Kutai.